A miRNA-based gene therapy nanodrug synergistically enhances pro-inflammatory antitumor immunity against melanoma. (1st January 2023) - Ma, Yawen; Lin, Huimin; Wang, Peng; Yang, Haocheng; Yu, Jie; Tian, Hao; Li, Tianyu; Ge, Shengfang; Wang, Yilong; Jia, Renbing; Leong, Kam W.; Ruan, Jing
Abstract: MicroRNA (miRNA)-based gene therapy is a robust approach to treating human cancers. However, the low target specificity and safety issues associated with viral vectors have limited the clinical use of miRNA therapeutics. In the present study, we aimed to develop a biocompatible nanocarrier to deliver the tumor suppressor miR-30a-5p for gene therapy of ocular melanoma. The quasi-mesoporous magnetic nanospheres (MMNs) were prepared by polyelectrolytes-mediated self-assembling Fe3 O4 nanocrystals; the cationic polymer capped quasi-mesoporous inner tunnels of the MMNs facilitate high miRNA loading and protect from nuclease degradation. Then, the outer layer of the MMNs was modified with a disulfide bond bridged very low molecular weight polyethyleneimine (PEI) network to form redox-responsive nanospheres (rMMNs) that enhance the miRNA payload and enable miRNA release under glutathione-dominant tumor microenvironment. The miR-30a-5p loaded rMMNs nanodrug (miR-30a-5p@rMMNs) upregulated miR-30a-5p level and inhibited malignant phenotypes of ocular melanoma by targeting the transcription factor E2F7 both in vitro and in vivo . Additionally, rMMNs act as an enhancer to increase cancer cell apoptosis by modulating M1-like macrophage polarization and activating Fenton reaction. Thus, the rMMNs is a promising miRNA carrier for gene therapy and could enhance pro-inflammatory immunity in melanoma and other cancers. Statement of significance: miR-30a-5p@rMMNs inhibited malignant phenotypes of ocular melanoma both in vitro and in vivo . The rMMNs promoted M1 macrophage polarization thus synergistically enhancing pro-inflammatory anti-tumor immunity against melanoma. The rMMNs showed no obvious toxicity under the injection dose. Graphical abstract: Image, graphical abstract